Religious minorities in Iraq: co-existence, faith and recovery after ISIS - Corticelli, Maria Rita (I. B. Tauris, 2022)
"The religious minorities of Iraq suffered immense violence at the hands of ISIS and they are now trying to rebuild their lives. In their own words, this book tells their stories of resilience against oppression, creativity in the darkest moments, and hope amidst death. Covering the experiences of the Christians, Kakais, Yezidis, Sunni Muslims and Shabaks, among others, this is an in-depth investigation that reveals how the different communities narrate their beliefs and deal with life and recovery in the aftermath of ISIS. Existing literature on the religious minorities in Iraq treats them in isolation as if they do not interact. This is the first book to show that a strong network between them operates in the absence of a strong civil society and based on a common desire to coexist, reconstruct their society and build peace. Over three years, the author visited religious and archaeological sites and interviewed more than one hundred people between representatives of the religious communities, academics, activists, politicians, policy makers and refugees. Among them are victims and persecutors, men, women and children, all who have been overwhelmed by the tragic events of the last few years. The author shows that all these groups are animated by the same desire for a new, more tolerant society and that their treatment of each other is nurtured by their shared experience of persecution and oppression"--